Nephrotoxic potency of antisera to three rat glomerular basement membrane glycoproteins. - Devulder, B (1978)
In a previous article, we cited studies which have allowed us to isolate diverse glycoproteins of the rat glomerular basement membrane (GMB) and to study their biochemical structures and antigenicity. This present study attempts to examine, using the heterologous nephrotoxic nephritis model (Masugi's nephritis) the nephrotoxicity of immune sera prepared from three of these glycoproteins: one fairly rich in collagen-like structures (A3), another lacking collagen-like structures (A1), and a third of intermediate composition (A2). The results obtained are discussed in relation to those already published concerning the nature of the GBM antigen(s) responsible for the nephrotoxicity of the sera.